Understanding Shakespeare Shakespeare comedy (Victoria : Learning Essentials, 2000)
Summary: This program investigates the nature of comedy by examining Shakespeare's'Much Ado About Nothing' and'The Tempest'. The presenters discuss the humour, wit and social satire in these plays, and also stress the essential seriousness of great comedy, with its power to advance moral and spiritual values.
Presenter: Alan Dilnot, Sue Fweng
Keywords: English literature; Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Comedies